Thermodynamics : an engineering approach - Cengel, Yunus A.; Cengel, Yunus A.; Boles, Michael A. (McGraw-Hill Education, 2015)
The eighth edition of the bestseller Thermodynamics: An Engineering Approach moves students toward a clear understanding and firm grasp of the basic principles of thermodynamics. This textbook communicates directly with tomorrow's engineers in a simple yet precise manner that encourages creative and imaginative thinking and is read by students with interest and enthusiasm all over the world."--Publisher's website